Meningkatkan Keterampilan Guru SMP Kota Palu dalam Merancang Pembelajaran PBL Berbasis Understanding by Design - Gamar Shamdas; Mohammad Jamhari; Mursito Bialangi; Nengah Kundera; Rizka Fardha (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
The community service program aims to use training and mentoring  to help teachers  at SMP Negeri 19 Palu, Central SSulawesi, become more adept at  creating UbD-based PBL classes. The main problem is teachers' low  competence in designing innovative learning, so interventions such as training, mentoring, and direct practice are needed. This activity is important in encouraging initiatives to raise the standard of education and teacher  pedagogy. This program employs interactive action research techniques in a qualitative manner. Data were collected from 15 teachers through product assessments and assessments of teacher involvement and skills. The results were analyzed descriptively and qualitatively. The activity’s outcomes demonstrate a  rise in teacher skills in designing learning using the UbD-based PBL model. 100% of the produced goods meet the "excellent" quality criteria . The findings from observations of teacher activities show that all teachers work well together, communicate, collaborate, help each other, take on a high level of responsibility in completing tasks, and play an active role in their groups. These findings indicate that training accompanied by mentoring helps teachers overcome obstacles to pedagogical competence. The logical consequence of this program has been a significant improvement in teachers' skills in designing innovative learning using UbD-based contextual problems. It is advised that this program be maintained and expanded to design contextual learning that prioritizes learning quality according to student needs.